1997
DOI: 10.1007/s11881-997-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of suffixed words: A comparison of reading disabled and nondisabled readers

Abstract: The present study was undertaken to measure and compare reading disabled and nondisabled readers" semantic and syntactic knowledge about derivational suffixes as a function of modality (reading versus listening) and as a function of the "neutrality" of the derivative (neutral versus nonneutral) . In the present study, neutrality refers to how straightforward and productive is the relationship between the root and derived form, with "completeness" qualifying as a neutral derivative and "completion" a nonneutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 20 publications
3
37
1
4
Order By: Relevance
“…The plots against Reading Age (Figures 1 and 2) show very clearly that dyslexic morphological development followed a normal course in which capacity to perform both implicit (sentence context) and explicit (analogy) tasks was dependent on the literacy level which had been achieved. This outcome agrees with previous findings by Carlisle (1987), Bryant et al (1997a, b;1998), Champion (1997) and Fowler and Liberman (1995) but contrasts with Elbro's (1989Elbro's ( , 1990 report of group differences in sentence analysis and morpheme reversal and completion tasks.…”
Section: Level 3: Morphographysupporting
confidence: 92%
“…The plots against Reading Age (Figures 1 and 2) show very clearly that dyslexic morphological development followed a normal course in which capacity to perform both implicit (sentence context) and explicit (analogy) tasks was dependent on the literacy level which had been achieved. This outcome agrees with previous findings by Carlisle (1987), Bryant et al (1997a, b;1998), Champion (1997) and Fowler and Liberman (1995) but contrasts with Elbro's (1989Elbro's ( , 1990 report of group differences in sentence analysis and morpheme reversal and completion tasks.…”
Section: Level 3: Morphographysupporting
confidence: 92%
“…This type of paradigm has been used in investigations of derivational morphology. Champion (1997) compared dyslexic 6th graders to chronological matched (CA) and reading age matched (RA) control groups on a task that involved extracting lexical-semantic information about inflected forms in an oral and reading condition. The dyslexic children were far more impaired than the control groups in the reading condition, relative to their age appropriate performance in the oral condition.…”
Section: Introductionmentioning
confidence: 99%
“…For Leong (1989), poor readers and spellers were slower at producing derived and base word forms than good readers or spellers, particularly when the words involved both phonological and orthographic changes from base to derived form. Champion (1997) established that, while poor readers differed from good readers in awareness of the semantic and syntactic aspects of derived forms, the differences were more pronounced in reading than in oral tasks. Fowler and Liberman (1995) found that poor readers differed from good readers in the oral production of words that undergo phonological shifts and that students' sensitivity to morphologically complex words in an oral production task was related to their reading and spelling abilities.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
“…Leong, 1989;Fowler & Liberman, 1995;Champion, 1997;Singson, Mahoney & Mann, 2000). Leong (1989) and Champion (1997) contrasted good and poor readers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation